The Relationship Between Big Five and Self-Control in Boxers: A Mediating Model - Zhang, Guodong; Chen, Xin; Xiao, Luxia; Li, Yun; Li, Bing; Yan, Zi; Guo, Liya; Rost, Detlef H. (Frontiers in Psychology, 2019)
The current study was aimed to shed some additional light on the relationship between the Big Five personality traits and self-control in boxers and investigates self-efficacy as a mediator between the two variables. Two hundred and ten boxers (age: M = 18.89, SD = 3.83; amount of boxing practice: M = 4.93 years, SD = 3.22; 76 male) of Chinese national athletes participated the study. Results showed a pronounced level of self-control. The higher the competitive level, the higher the level of self-control. There were significant correlations among the Big Five, self-control, and self-efficacy. Self-efficacy mediated the relationship between the Big Five personality traits and self-control.